2023
DOI: 10.1002/cbic.202300503
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the RAGE‐Induced Inflammatory Response: Peptoids as RAGE Antagonists

Mihyun Lim Waugh,
Lauren M. Wolf,
James P. Turner
et al.

Abstract: While the primary pathology of Alzheimer’s disease (AD) is defined by brain deposition of amyloid‑β (Aβ) plaques and tau neurofibrillary tangles, chronic inflammation has emerged as an important factor in AD etiology.  Upregulated cell surface expression of the receptor for advanced glycation end‐products (RAGE), a key receptor of innate immune response, is reported in AD.  In parallel, RAGE ligands, including Aβ aggregates, HMGB1, and S100B, are elevated in AD brain.  Activation of RAGE by these ligands trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In this regard, some new efforts have been focused on the development of inhibitors of RAGE binding and signaling, as well as those that could be useful in the treatment of RAGE activation-associated diseases [202][203][204][205].…”
Section: Therapeutic and Diagnostic Potential Of The Rage Axismentioning
confidence: 99%
“…In this regard, some new efforts have been focused on the development of inhibitors of RAGE binding and signaling, as well as those that could be useful in the treatment of RAGE activation-associated diseases [202][203][204][205].…”
Section: Therapeutic and Diagnostic Potential Of The Rage Axismentioning
confidence: 99%
“…Studies have shown novel therapeutic opportunities of peptidomimetics modulating cell signaling pathways [23,24], neuroinflammation [25,26], oxidative stress [27], apoptosis [28,29], and depression [21,30,31]. For example, peptoids such as RAGEs (receptor for advanced glycation end-products) antagonists can modulate the RAGE-induced inflammatory response [26]. A structure-based development of new peptidomimetic cyclic compounds was conducted for the PSD-95 PDZ3 domain, which is a promising therapeutical target for depression [32].…”
Section: Introductionmentioning
confidence: 99%